Museologia, Educação e Ciência: a coleção de didática de paleontologia do Museu Paraense Emilio Goeldi - ANTUNES, Bruna de Campos (2019)
The didactic collections can be defined as collections intended for teaching, demonstrations and training, and for Paleontology these are critical, as they allow the effective and immediate contact with fossils, representatives of a past history. However, the study related to this science is sometimes limited to the society, mainly restricted to the academic world. In order to arouse interest in Paleontology in primary and secondary school students, and fill the gaps in education, a MPEG’s Paleontology Didactic Collection was organized, which went through curatorial steps such as: mechanical preparation (cleaning); identification (using morphological aspects); documentation; and storage readjustment – from wooden drawers to steel cabinets lined with foams. This collection currently has around 153 registers, among unique samples and sets, with approximately 1,000 fossils between vertebrates and invertebrates, which more than 90% comes from Pirabas Formation deposits, the most important geological unit of the state of Pará, and recognized by its fossiliferous abundance. Most of the collection consists of mollusks, gastropods, echinoderms and rib fragments (post-cranial fragments), as well as vertebrae and teeth. The collection is used in educational activities, currently mainly in scientific communication events conducted by MPEG, and illustrative classes at Universities. The didactic collection has been seen as a means of information democratization and research conducted by MPEG, because it makes Amazon’s fossil heritage accessible to teachers and students of primary and secondary education, strengthening the educational role of this institution.